Current approaches on the roles of lactic acid bacteria in crop silage. Issue 1 (5th December 2022) - Guo, Xusheng; Xu, Dongmei; Li, Fuhou; Bai, Jie; Su, Rina
Abstract: Lactic acid bacteria (LAB) play pivotal roles in the preservation and fermentation of forage crops in spontaneous or inoculated silages. Highlights of silage LAB over the past decades include the discovery of the roles of LAB in silage bacterial communities and metabolism and the exploration of functional properties. The present article reviews published literature on the effects of LAB on the succession, structure, and functions of silage microbial communities involved in fermentation. Furthermore, the utility of functional LAB in silage preparation including feruloyl esterase‐producing LAB, antimicrobial LAB, lactic acid bacteria with high antioxidant potential, pesticide‐degrading LAB, lactic acid bacteria producing 1, 2‐propanediol, and low‐temperature‐tolerant LAB have been described. Compared with conventional LAB, functional LAB produce different effects; specifically, they positively affect animal performance, health, and product quality, among others. In addition, the metabolic profiles of ensiled forages show that plentiful probiotic metabolites with but not limited to antimicrobial, antioxidant, aromatic, and anti‐inflammatory properties are observed in silage. Collectively, the current knowledge on the roles of LAB in crop silage indicates there are great opportunities to develop silage not only as a fermented feed but also as a vehicle of delivery of probiotic substances for animal health and welfare in the future. Abstract : The present article reviews published literature on the effects of LAB on the succession, structure, and functions of silage microbial communities involved in fermentation. In addition, the utility of functional LAB in silage preparation have been described.